What Type of Oral Corrective Feedback do Chilean EFL Young Learners Prefer? - Pablo Aedo; Claudia Millafilo (Asociación Colombiana de Profesores de Ingles, 2022)
This article presents the perspectives of a Chilean group of young learners of English as a foreign language with respect to the types of corrective oral feedback when making a spoken mistake and the reasons for their preferences. By means of a qualitative exploratory study, the views of 20 students were collected through a specially adapted scale and a focus group. The data from the scales were analyzed with descriptive statistics while the focus groups were interpreted with the content analysis technique. The results suggest that students appreciate teacher's correction and feedback when done carefully and clearly and considering students' affective domains such as beliefs and motivation. They also show a tendency towards the strategies of recast and repetition. On the other hand, they prefer less the use of metalinguistic feedback and elicitation strategies. In addition, this experience suggests that children are capable of reflecting on their learning processes, so it is urged that children be given an active participatory role in the development of methodologies and strategies to capture the voices of the real potential beneficiaries of these.